2021
DOI: 10.3390/s21082681
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Based Power Management for Congested IoT Networks

Abstract: With constantly increasing demand in connected society Internet of Things (IoT) network is frequently becoming congested. IoT sensor devices lose more power while transmitting data through congested IoT networks. Currently, in most scenarios, the distributed IoT devices in use have no effective spectrum based power management, and have no guarantee of a long term battery life while transmitting data through congested IoT networks. This puts user information at risk, which could lead to loss of important inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In the present study, the mean Hb was 11.25±2.57, WBCs, PLT, ALT and AST were 14.37±6.21, 232.71±115.9, 54.6±34.88 and 84.6±41.55 respectively, also BUN and creatinine were (16.95±12.36 and 0.56±0.41 respectively), +ve CRP in 85% and PCT 6.7%. Our findings are in agreement to the results of the recent study of Besher et al (11) , which demonstrated that the laboratory investigation among study group showed normal Hg, platelet (PLT) and leukocytosis in CBC, and increasing liver enzymes (AST).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the mean Hb was 11.25±2.57, WBCs, PLT, ALT and AST were 14.37±6.21, 232.71±115.9, 54.6±34.88 and 84.6±41.55 respectively, also BUN and creatinine were (16.95±12.36 and 0.56±0.41 respectively), +ve CRP in 85% and PCT 6.7%. Our findings are in agreement to the results of the recent study of Besher et al (11) , which demonstrated that the laboratory investigation among study group showed normal Hg, platelet (PLT) and leukocytosis in CBC, and increasing liver enzymes (AST).…”
Section: Discussionsupporting
confidence: 93%
“…As a result, the wireless spectrum is becoming an essential and scarce resource. Moreover, there are so many technologies coexisting together that the problems of interference, channel congestion, data collisions, and unbalanced spectrum usage become a challenge, which drastically reduces overall network performance and user experience [25,26]. In this sense, we present some works discussing solutions to this challenge.…”
Section: Wireless Spectrum Managementmentioning
confidence: 99%
“…Providing quality of service (QoS) is one of the most significant challenges [ 9 , 10 , 11 , 12 , 13 , 14 ]. Furthermore, considering the use of wireless networks and the presence of network congestion, this challenge becomes more difficult to solve [ 9 , 15 ]. For example, various healthcare applications that send and receive electrocardiogram (ECG) data can cause a significant increase in data traffic, which can lead to network congestion.…”
Section: Introductionmentioning
confidence: 99%